Responsive Law of the National Sharia Council of the Indonesian Ulema Council’s Fatwa on Permissibility of Electronic Money - Marwal, Muhammad Ilyas; Munir, Badrul; Marwal, M. Rafid; Ilyas, Muhammad Fadhlirobby (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research examines the role of the fatwa of the National Sharia Council of the Indonesian Ulema Council regarding the permissibility of using electronic money as a law responsive to socio-economic phenomena and its impact on the economic practices of Muslim communities in Indonesia. With a descriptive-analytical qualitative approach, this research uses primary data from in-depth interviews and secondary data from official documents to understand the implementation and impact of the fatwa. The research results show that the DSN MUI fatwa provides important legal certainty for Muslims, ensuring that the use of electronic money follows Sharia principles such as the prohibition of usury, gharar, and haram transactions. In addition, this fatwa emphasizes security and transparency in transactions, increasing public trust in the digital financial system and supporting financial inclusion by enabling access to modern financial services for people previously unreachable by conventional banking. In conclusion, the DSN MUI fatwa supported the adaptation of Islamic law to the development of modern financial technology, ensuring the integration of technological innovation in the lives of Muslims without sacrificing their religious values. This research was conducted without conflict of interest, with all processes being independent and objective to ensure scientific integrity.